Avaliação do lodo de estação de tratamento de esgoto como meio carreador e de proteção do agente de controle biológico Trichoderma harzianum para aplicação na agricultura - Leite, Priscila Polaquini de Macedo (Universidade Federal de São Carlos, 2026)
The growing demand for food, driven by population growth, has intensified the need for more productive and environmentally sustainable agricultural systems due to the environmental and human health risks associated with conventional agricultural practices. In this context, biocontrol agents have emerged as promising alternatives to conventional agrochemicals, particularly fungi of the Trichoderma genus, which are widely recognized for their ability to control phytopathogens and promote plant growth. However, when applied to the aerial parts of plants, these microorganisms are sensitive to ultraviolet radiation and temperature fluctuations, factors that reduce their viability and effectiveness. Therefore, this study aimed to develop a sewage sludge-based granule for the incorporation of the biocontrol agent Trichoderma harzianum, evaluating its potential as a carrier matrix and as a physical barrier against UV radiation, for application either as a water-based suspension pulverized onto the phyllosphere or as whole granules applied directly to the soil. The granules were produced using sewage sludge and glycerol and were subsequently characterized regarding their physicochemical, mechanical, and biological properties. The material exhibited biocompatibility with the fungus, causing no inhibition halo formation and allowing fungal growth and colonization after the granulation process. Furthermore, the granules showed high mechanical resistance, with an average maximum compressive force of 21.46 ± 1.24 N and a mass loss of approximately 0.1% in the abrasion test. UV-Vis spectroscopy analysis revealed high absorption in the ultraviolet region, particularly between 260 and 350 nm, suggesting the potential of the material to act as a partial barrier against incident UV radiation. Overall, the results indicate that sewage sludge has potential as a carrier matrix for Trichoderma harzianum, contributing to the development of more sustainable agricultural formulations aligned with the principles of the circular economy, such as waste valorization and the return of nutrients to the soil.
Evaluation of sewage sludge from wastewater treatment plants as a carrier and protective medium for the biological control agent Trichoderma harzianum for agricultural application
Keywords: Lodo de esgoto; Trichoderma; Proteção UV; Sewage sludge; Trichoderma harzianum; biocontrol agents; UV protection; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::TRATAMENTOS E APROVEITAMENTO DE REJEITOS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::TRATAMENTOS E APROVEITAMENTO DE REJEITOS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE PROCESSAMENTO DE PRODUTOS AGRICOLAS::PRE-PROCESSAMENTO DE PRODUTOS AGRICOLAS; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA; 2. Fome Zero e Agricultura Sustentável; 6. Água Potável e Saneamento